PENGARUH NET PROFIT MARGIN DAN DIVIDEN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2016-2020 (SUB SEKTOR MAKANAN-MINUMAN DAN FARMASI) - Livia Ursula; Jhon Raphael Saragih (ITB AAS INDONESIA, 2022)
The purpose of this study is to determine the effect of Net Profit Margin and dividends on stock prices in manufacturing companies listed on the BEI 2016-2020 (sub sector food–beverage and pharmacy). This research method uses quantitative methods. This study uses the NPM indicator. Dividend indicator using DER (Dividend PayOut Ratio). This study uses 11 manufacturing companies listed on the Bursa Efek Indonesia period 2016-2020 (sub sector food–beverage and pharmacy) as samples. Based on this research, it was found that NPM has no effect on stock prices, Dividend has no effect on stock prices, and simultaneously NPM and Dividend do not effect stock prices in manufacturing companies listed on the BEI 2016-2020 (sub sector food–beverage and pharmacy).